High sensitivity flexible double square winding eddy current array for surface micro-defects inspection - Ma, Qiuping; Gao, Bin; Tian, G.Y.; Yang, Changrong; Xie, Lian; Chen, Kefan (Sensors and actuators. A. Physical., 2020)
[Display omitted] •The magnetic field diverges around the excitation winding and covers a large. area. It has the capability to micro-defects inspection in this magnetic field.•The eddy current field with transmitting-receiving-transmitting structure on the specimen is rectangular and uniform.•Novel flexible sensor array has a high sensitivity and capability with orientational defects detection. High sensitivity surface micro-defects nondestructive testing on the complex geometric sample is a critical filed for the scientific and industrial community. This paper proposes a novel flexible eddy current sensing system that incorporates double square winding excitation with a multi detection flexible array for cracks inspection. The new structure consists of two square drive traces located in the separated layers while the pick-up traces are sandwiched between the drive traces. In particular, two excitation coils are in parallel and multi-turns thin spiral rectangular coils are detectors while the whole probe constitutes a transmitting-receiving-transmitting structure. The new structure offers capability and sensitivity for micro defects as well as directional defects inspection. The theoretical derivation based on magnetic circuit principles has been developed for analysis and interpretation of the results. Both numerical simulation and experiments on defects detection with different defect sizes and orientations have been supplemented to validate the reliability and efficiency of the proposed system.